Generated outcomes in risky choice reveal biased sampling and sequential dependencies. - Spicer, Jake; Li, Yun-Xiao; Castillo, Lucas; Falbén, Johanna K.; Qian, C. Stella; Sanborn, Adam N. (Communications Psychology, 2026)
Recent decision-making models have explained behaviour using mental sampling mechanisms, but there is still little agreement on the specific sampling process, such as whether sampling rates match true probabilities. Here, we seek to trace the sampling process using generation tasks: in two experiments using general online samples (Ns = 52, 51), participants repeatedly produced potential outcomes from pairs of monetary gambles before choosing between them. Results found over-generation of rarer outcomes and under-generation of common outcomes overall, but not in initial responses, as well as avoidance of direct repetitions. Participants also tended to select options with higher average utility across their responses, implying generations guided choice. These findings suggest systematic biases in the information people may consider before a choice, and the influence that this can have on subsequent decisions, carrying implications for mental sampling models of this behaviour. We thus suggest explicit generation is a valuable method to access underlying choice processes, offering new assessments of existing theories of decision making. This study examined what information people may consider before a choice by asking them to repeatedly generate its possible outcomes. Participants overgenerated rare events and avoided direct repetitions, suggesting biases in what comes to mind.